A new name for an old practice: vigilante in South-western Nigeria - (:unkn) unknown (My University, 2008)
It is often considered probable that the recent rise of vigilante groups in Nigeria means an erosion of the state monopoly of legitimate violence as well as a marked decline in state sovereignty over the national territory. However, this conclusion does not take into consideration the fact that in Nigeria 'vigilante' is a term initially proposed by the police in the mid-1980s as a substitute for an older practice known in the western part of the country since the colonial period as the 'hunter guard' or 'night guard' system. Hence, instead of looking at vigilante groups as a response to a supposed increase in crime or a supposed decline of the police force, we should consider them - initially at least - as a first attempt to introduce forms of community policing in order to improve the appalling image of the police. As such, in south-western Nigeria 'vigilante' is a new name for an old practice of policing that should be considered in an extended timeframe (from the 1930s onward), a period in which violent crime has been perceived as a potential danger. Finally, within the ongoing debate on the 'privatization of the state' in Africa, non-state policing in Nigeria testifies to a continuum existing since the colonial period rather than to the appearance of new phenomena in the 1980s or the 1990s.
Keywords: African Research